Analisis Kesesuaian Lahan Permukiman di Kecamatan Kambu Kota Kendari - Satriyo Dwi W; La Ode Safuan; Hasbullah Syaf (Jurnal Perencanaan Wilayah, 2022)
Residential areas in Kambu District require land suitability. This study aims to (1) analyze the suitability of residential land in the Kambu sub-district, Kendari city, (2) analyze the suitability of the settlement location in the Kambu sub-district based on the suitability and availability of the location according to the Kendari City Spatial Plan (RTRW). The method used in this research is qualitative analysis, and overlay analysis. The results of the study show, (1) The suitability of residential land in the Kambu sub-district, Kendari City for the very suitable category for residential areas of 1,106.03 ha or 49.86 percent; (2) The suitability of the location for settlements in Kambu District is based on the suitability and availability of the location according to the Kendari City Spatial Planning (RTRW) covering an area of 402.88 Ha or 18.16 percent.Keywords: Suitability, Settlements, and OverlaysKawasan permukiman di Kecamatan Kambu memerlukan kesesuaian lahan. Penelitian ini bertujuan (1) Menganalisis kesesuaian lahan permukiman di wilayah Kecamatan Kambu Kota Kendari, (2) Menganalisa kesesuaian lokasi untuk permukiman di Kecamatan Kambu berdasarkan kesesuaian dan ketersediaan lokasi menurut Rencana Tata Ruang Wilayah (RTRW) Kota Kendari. Analisis data yang digunakan dalam penelitian ini adalah analisis kualitatif, dan analisis overlay. Hasil penelitian menunjukkan (1) Kesesuaian lahan  permukiman di wilayah Kecamatan Kambu Kota Kendari untuk kategori sangat sesuai bagi permukiman penduduk seluas 1.106,03 Ha atau 49,86 persen; (2) Kesesuaian lokasi untuk permukiman di Kecamatan Kambu berdasarkan kesesuaian dan ketersediaan lokasi menurut Rencana Tata Ruang Wilayah (RTRW) Kota Kendari seluas 402,88 Ha atau 18,16 persen.Kata Kunci : Kesesuaian, Permukiman, dan Overlay